مقاربة سيكولوجية للتحرش الجنسي وتداعياته النفسية - ميروح كريمة (University of Eloued جامعة الوادي, 2024)
ملخص: يعتبر التحرش الجنسي من أخطر أشكال العنف الذي يمكن أن يتعرض له الفرد، حيث يشكل عامل ضغط يخلف آثارا جسيمة على الصحة النفسية والجسمية للضحية، ويعد من القضايا التي لا تزال تشغل حيزا واسعا من إهتمام الباحثين في مجال علم النفس وعلم الإجتماع، لكونه ينتهك كرامة الإنسان بمشاعر الإذلال والإحتقار التي يولدها بدافع تـأثير القـوة والنـوع والمكانـة داخـل المستويات التنظيميـة، والاجتماعيـة، والثقافيـة، والفرديـة، كما يعد إقتحاما للحدود النفسية والجسمية للضحية، واعتداء على كينونتها، فيقوض بذلك رفاهيتها النفسية، ويشعرها بعدم الأمان، وهو لا يقتصر على مجتمع بذاته، كما لا يخص نوعا أو شريحة إجتماعية دون أخرى، لكن الإناث أكثر عرضة للتحرش الجنسي من غيرها، ومهما كان الشكل الذي يتخذه فإن ردود الضحايا اتجاهه تتباين بحسب طبيعة شخصية الضحية والظروف المحيطة بها، ومن خلال هذه الورقة البحثية سنسعى لتقديم مقاربة سيكولوجية لظاهرة التحرش الجنسي بتحديد مفهومه، وأشكاله، وسمات شخصية كل من المتحرش والضحية، ناهيك عن تداعياته السيكولوجبة. Abstract: Sexual harassment is one of the most dangerous forms of violence to which an individual can be exposed, as it constitutes a pressure factor that has serious effects on the mental and physical health of the victim. It is one of the issues that still occupies a wide range of interest among researchers in the field of psychology and sociology, For violating human dignity with the feelings of humiliation and contempt that it generates out of the influence of power, gender and status within the organizational, social, cultural and individual levels, as well as breaking into the psychological and physical limits of the victim, and assaulting her being. This undermines her psychological well-being and makes her feel insecure, and it is not limited to a society itself, nor does it concern one type or social segment without the other, but females are more vulnerable to sexual harassment than others, Whatever form it takes, the responses of the victims towards it vary according to the nature of the victim's personality and the circumstances surrounding it, and through this research paper we will seek to provide a psychological approach to the phenomenon of sexual harassment by defining its concept and forms. The personal characteristics of both the harasser and the victim, not to mention its psychological implications
Keywords: تحرش جنسي; تداعيات نفسية للتحرش; أشكال التحرش; هيمنة ذكورية; ضغط النفسي; Sexual harassment; Psychological repercussions of harassment; Forms of harassment; Male domination; Psychological stress